Electrophysical properties of singlecrystal silicon sequentially doped with sulfur and zinc impurity atoms - M.K. Haqqulov (Genius Journals, 2023)
The paper studies electro physical properties of single crystal silicon after gradual (firstsulfur, afterwards -zinc) diffusion of impurity atoms of sulfur and zinc. The authors investigated how the Si2ZnS -structured binary compounds form in the crystal lattice of silicon and also studied the physical mechanisms of how additional thermal treatment might influence the process of formation of clusters.
Keywords: silicon; siliconsulfur; cluster; impurity